Implementasi Algoritma One Time Pad (OTP) untuk Pengamanan Pesan Short Message Service (SMS) - Batubara, Muhammad Iqbal (MEANS (Media Informasi Analisa dan Sistem), 2019)
The operating system for mobile devices is growing. Android is a mobile operating system that is now very popular and widely used by people. Android is also a software-based operating system that can be developed in open source so that many developers are now participating in developing applications for Android. For the purposes of security aspects, Android also has provided specifically for cryptographic functions, such as encryption, description, and so on. Message message service (SMS) is a very popular communication technology. By using SMS someone can exchange information. In this case the SMS sent will be encrypted in the development of an Android-based cell phone program for sending SMS messages. The test results show that the use of the One Time Pad (OTP) algorithm can encrypt short messages with text to the destination number. The application can help users to send short messages in a safe, fast, and easy place.